Phenotypic and molecular assessment of seven patients with 6p25 deletion syndrome: Relevance to ocular dysgenesis and hearing impairment - Ritch Robert; Munier Francis; Addison Mark K; Jaafar Mohamad S; Gould Douglas B; MacDonald Ian M; Walter Michael A (BMC, 2004)
Abstract Background Thirty-nine patients have been described with deletions involving chromosome 6p25. However, relatively few of these deletions have had molecular characterization. Common phenotypes of 6p25 deletion syndrome patients include hydrocephalus, hearing loss, and ocular, craniofacial, skeletal, cardiac, and renal malformations. Molecular characterization of deletions can identify genes that are responsible for these phenotypes. Methods We report the clinical phenotype of seven patients with terminal deletions of chromosome 6p25 and compare them to previously reported patients. Molecular characterization of the deletions was performed using polymorphic marker analysis to determine the extents of the deletions in these seven 6p25 deletion syndrome patients. Results Our results, and previous data, show that ocular dysgenesis and hearing impairment are the two most highly penetrant phenotypes of the 6p25 deletion syndrome. While deletion of the forkhead box C1 gene (FOXC1) probably underlies the ocular dysgenesis, no gene in this region is known to be involved in hearing impairment. Conclusions Ocular dysgenesis and hearing impairment are the two most common phenotypes of 6p25 deletion syndrome. We conclude that a locus for dominant hearing loss is present at 6p25 and that this locus is restricted to a region distal to D6S1617. Molecular characterization of more 6p25 deletion patients will aid in refinement of this locus and the identification of a gene involved in dominant hearing loss.